Black holes from multiplets of scalar fields in 2+1-and 3+1 dimensions - Mazharimousavi, S. Habib; Halilsoy, M. (Springer, 2016)
We obtain classes of black hole solutions constructed from multiplets of scalar fields in 2 + 1/3 + 1 dimensions. The multi-component scalars do not undergo a symmetry breaking so that only the isotropic modulus is effective. The Lagrangian is supplemented by a self-interacting potential which plays significant role in obtaining the exact solutions. In 2 + 1/3 + 1 dimensions, a doublet/triplet of scalars is effective, which enriches the available black hole spacetimes and creates useful Liouville weighted field theoretic models.
Keywords: Particle Physics Models; Klein-Gordon Equations; Global Monopoles; Kink Solution; 2+1 Gravity; Inflation; Cosmology; Energy; Geometry; Space